1559. Hematopoietic Cell Transplantation with Post-transplant Cyclophosphamide: Impact of Donor Type on Pre-engraftment Blood-Stream Infections. (26th November 2018) - Oltolini, Chiara; Greco, Raffaella; Galli, Laura; Lorentino, Francesca; Xue, Elisabetta; Stanghellini, Maria Teresa Lupo; Clerici, Daniela; Giglio, Fabio; Peccatori, Jacopo; Bernardi, Massimo; Corti, Consuelo; Scarpellini, Paolo; et al.
Abstract: Background: The aim of the study was to estimate the cumulative incidence of pre-engraftment blood stream infections (PE-BSI), its predictive factors and the infection-related mortality (IRM) after hematopoietic cell transplantation (HCT) from any donor type, with post-transplant cyclophosphamide (PT-Cy). Methods: Retrospective cohort study on 235 adults who underwent peripheral blood HCT from every donor type with PT-Cy platform, from 2013 to 2017 at San Raffaele Scientific Institute. The Poisson regression was used to estimate the crude incidence rate (IR) of PE-BSI. The Fine-Gray competing risk model was applied to estimate the cumulative incidence function (CIF) of the first PE-BSI and its predictive factors and of IRM. Results: Patients' characteristics are reported in Table 1. During 5, 316 person-days of follow-up (PDFU), 77 PE-BSI episodes occurred in 72 patients: IR = 1.45 per 100-PDFU [95% confidence interval (95% CI) 1.13–1.77]. The median time to PE-BSI was 13 days (IQR: 7–17) and the estimated CIF at 28 days was 32% (95% CI: 26–39%); no differences in CIF according to donor type [30% vs. 34% vs. 32% in match-related, match-unrelated and haploidentical donor, respectively; Gray's test: P = 0.968]. Among the 87 isolated pathogens, 60% were Gram-positive bacteria (GPB), 39% Gram-negative bacteria (GNB) and 1% nontuberculous mycobacteria. CIFs of GNB and GPB PE-BSI by type of donor are shown in Figure 1. By multivariate analysis (Table 2), after adjustment for age, sex, year of HCT, donor type and disease phase at HCT, the CIF of any PE-BSI was higher in subjects with absolute neutrophils count ≤500 for ≥7 days before HCT [adjusted hazard ratio (AHR) = 2.90] and in multi-drug resistant (MDR) GNB rectal carriers before HCT [AHR = 2.68]. These covariates were confirmed as independent factors also for GNB PE-BSI. Overall, IRM at 30 days was 5% (95% CI: 2–8%) with no differences by donor type (Gray's test: P = 0.106). Conclusion: HCT with PT-Cy platform showed a 32% of cumulative incidence of PE-BSI at 28 days and donor type did not affect its occurrence, which was conversely increased by prolonged and severe neutropenia and MDR GNB rectal carriage before HCT. Haploidentical setting did not retain a higher IRM at 30 days than match-related and match-unrelated donors. Disclosures: All authors: No reported disclosures.